Determinants of Students’ Perceptions and Satisfaction with Virtual Learning Environments: Evidence from a Peruvian Public University - Mamani-Flores, Adderly; et al. (European Journal of Social Science Education and Research, 2026)
This study analyzes students’ perceptions of virtual learning environments used in academic training at the Faculty of Social Sciences during 2023. A quantitative, cross-sectional design was employed, using a structured survey administered to students from the professional programs of Anthropology, Sociology, Tourism, Social Communication, and Art. The instrument assessed key dimensions such as accessibility, interactivity, content quality, perceived effectiveness, proposed improvements, and overall satisfaction with virtual learning platforms. The results indicate heterogeneous perceptions across programs; however, flexibility, convenience, and ease of access to academic resources were consistently identified as the main advantages of virtual learning. Videoconferencing platforms with high levels of interoperability were reported as the most frequently used and preferred tools for instructional delivery. Overall, students reported predominantly positive experiences and a generally satisfactory level of acceptance of virtual learning environments. These findings provide relevant empirical evidence to inform the optimization of virtual educational platforms and support the adaptation of teaching strategies to better align with students’ academic needs and expectations.
Keywords: Behaviors, students, digital environments, perception, technology, online education, e-learning.